“Dekapan Kesakitan Tuhan” Dalam Kitab Para Nabi Sebagai Model Fatherhood Leadership: "God's Pain Embrace" In The Book of The Prophets as The Fatherhood Leadership Model - Sri Wahyuni Kusradi; Marlon Butarbutar; Jeane Paath (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2021)
This article wants to examine how God “embracing pain” as the Father continues to lead meekly even when God's people rebel and hurt His heart. For this reason, this study uses a descriptive qualitative method to describe the topic through words about the main ideas reported and bibliologically it will be examined regarding the "embrace of God's pain" which shows God's fatherhood leadership as written in the books of the prophets. So from these findings, it can finally become one of the leadership models of God's servants today.